Comparative diversity, relative abundance, and functional genes of bacterial community in a semi-closed marine fish hatchery between dry and wet seasons - Sutra, Jumria (2021)
Aquaculture has developed rapidly to become one of the most important food industries in the world. In recent years, increases in demands for local and exports markets of high-value fish species such as groupers (Epinephelus sp.) and Asian seabass (Lates calcarifer) have encouraged hatcheries to produce more fry to supply the demand from farmers. The increasing trend to develop large-scale production has led to intensive marine aquaculture practices, thus vulnerable to disease outbreaks that affects the quality of fry production. This study investigates the bacterial diversity and its functional genes that present in a semi-closed marine fish hatchery ecosystem between dry and wet seasons, by implementing amplicon metagenomics using Next-Generation Sequencing (NGS). The intestinal samples were collected from different sizes of tiger groupers (n = 9, 16.37 ± 5.46 cm, 54.00 ± 44.03 g and n = 9, 20.86 ± 8.73 cm, 133.43 ± 158.15 g for dry and wet season respectively) and Asian seabass (n = 10, 14.27 ± 4.45 cm, 41.93 ± 35.12 g and n = 13, 16.13 ± 6.83 cm, 60.45 ± 55.07 g for dry and wet season, respectively) as well as the culturing water (10 L), before proceeded to DNA extraction. The extracted DNA were then subjected to 16S rRNA amplicon sequencing using Illumina Miseq platform, followed by determination and comparison of the bacterial diversity, abundance and functional genes between both seasons. Selected physicochemical and seasonal parameters were also determined. Results revealed that gut microbiota of the Asian seabass were dominated by phylum Proteobacteria and order Vibrionales during both seasons. Meanwhile, gut microbiome of tiger groupers shifted from domination of phylum Firmicutes and order Clostridiales during the dry season to Proteobacteria and Lactobacillales during the wet season. Water samples were dominated by phylum Proteobacteria and order Stramenopiles in dry season but shifted to phylum Proteobacteria and order Flavobacteriales in the wet season. Total dissolved solid (TDS), water temperature (T), conductivity (C), salinity (S), ammonia (NH4), nitrite (NO2), nitrate (NO3), sulphate (SO4), average temperature (AT) and average rainfall (AR) showed significant different between dry and wet season. Proteobacteria, Firmicutes and Fusobacteria showed correlation towards the C, SO4, T, PO4, AR, AH and AT during the dry season, meanwhile phylum Bacteroidetes, Fusobacteria, SBR1093, WPS-2 and Verrucomicrobia showed strong correlation towards all environmental parameters during wet season. PICRUSt revealed functions that dominantly present in the tropical marine fish hatchery were metabolism, genetic information processing, environmental information processing, cellular process and human diseases. Remarkably, SIMPER analysis showed several potential metagenomics biomarker genes such as K03406, K06147 and K03088 in comparing microbiota between dry and wet season which can be utilised to be an indicator for the tropical marine fish hatchery environments. This study highlighted the dominant taxa and their putative function that dominated tiger grouper and Asian seabass as well as water samples in dry and wet season with the implementation if 16S amplicon approach better determination of the microbial profiles in the aquaculture systems.